Implementation of Proportionality and Professionalism Principles in Public Online Complaint Services - Nursyam, Andi Resky; Arake, Lukman; Jumriani Nawawi (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study examines the principles of proportionality and professionalism of government apparatus in implementing the online public complaint and aspiration services (LAPOR SP4N) in Bone Regency, Indonesia, with a focus on its alignment with maqāṣid al-syarī‘ah. Using a qualitative approach, the research evaluates both legal frameworks and operational practices of the service, revealing that the system, though legally grounded in local regulations, faces challenges such as limited human resources, insufficient technological infrastructure, and delayed responses. The study further explores how the maqāṣid al-syarī‘ah framework, particularly the principles of ḥifẓ al-dīn (protection of religion), ḥifẓ al-nafs (protection of life), ḥifẓ al-‘aql (protection of intellect), ḥifẓ al-māl (protection of wealth), and ḥifẓ al-nasl (protection of lineage), is integrated into public administration, ensuring ethical governance and the welfare of the community. The findings highlight how proportionality and professionalism are operationalized through clear division of duties, ethical public communication, and efficient budget management. However, improvements in the speed of responses, digital literacy of human resources, and transparency are essential for enhancing service effectiveness. The research contributes to the discourse on integrating Islamic governance principles in modern public administration, offering insights for more inclusive and accountable governance systems.